A clinical review of GLP-1 receptor agonists: efficacy and safety in diabetes and beyond - Lalita Prasad-Reddy; Diana Isaacs (BioExcel Publishing Ltd, 2015)
The prevalence of type 2 diabetes is increasing at an astounding rate. Many of the agents used to treat type 2 diabetes have undesirable adverse effects of hypoglycemia and weight gain. Glucagon-like peptide-1 (GLP-1) receptor agonists represent a unique approach to the treatment of diabetes, with benefits extending outside glucose control, including positive effects on weight, blood pressure, cholesterol levels, and beta-cell function. They mimic the effects of the incretin hormone GLP-1, which is released from the intestine in response to food intake. Their effects include increasing insulin secretion, decreasing glucagon release, increasing satiety, and slowing gastric emptying. There are currently four approved GLP-1 receptor agonists in the United States: exenatide, liraglutide, albiglutide, and dulaglutide. A fifth agent, lixisenatide, is available in Europe. There are important pharmacodynamic, pharmacokinetic, and clinical differences of each agent. The most common adverse effects seen with GLP-1 therapy include nausea, vomiting, and injection-site reactions. Other warnings and precautions include pancreatitis and thyroid cell carcinomas. GLP-1 receptor agonists are an innovative and effective option to improve blood glucose control, with other potential benefits of preserving beta-cell function, weight loss, and increasing insulin sensitivity. Once-weekly formulations may also improve patient adherence. Overall, these are effective agents for patients with type 2 diabetes, who are either uncontrolled on metformin or intolerant to metformin.